Electrolyte degumming of crude vegetable oil - Nsiah, Adams (2015)
A thesis submitted to the Department of Food Science and Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF SCIENCE IN FOOD SCIENCE AND TECHNOLOGY. 2012